PENGARUH TRANSAKSI PIHAK BERELASI TERHADAP PENGHINDARAN PAJAK DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MODERASI - Nindita Nindita; Y. Agus Bagus Budi N (ITB AAS INDONESIA, 2022)
The purpose of this research is to examine the effect of independent variable namely Related party asset and liability transaction on tax avoidance with earning management as moderating variable. The research sample was 57 manufacturing companies listed on Indonesia Stock Exchange during the 2015-2019 period and was carried out using purposive sampling method. The calculation tool used to perform data analysis in this study is SPSS v.25. The research process was carried out through multiple regression analysis and moderated regression analysis (MRA). The results showed that there was an effect of asset and liability transactions between related parties on tax avoidance. The earnings management variable is only able to stregthen the effect of asset transactions between related parties on tax avoidance. Earnings management activities do not have an influence on liability transactions between related party on tax avoidance. Keywords : earning management, tax avoidance, related party asset transaction, related party liability transaction